Autonomy Building Through Peer Tutoring: Second Language Students Engage in Literacy Learning (LEARNing Landscapes, 2007)
Research indicates that direct instruction of literacy skills benefits all learners, especially second language learners and students with learning challenges; however, students become disengaged when skills are taught through repetitive drill and skill practice in isolation from meaningful contexts. This article examines the critical pedagogy of an elementary classroom teacher as she engaged students in a peer tutoring reading program that developed learners’ autonomy and self-esteem.
Keywords: peer tutoring; autonomy; elementary school; student engagement; self-esteem; second language learner